Contamination of heavy metals and other organic pollutants in Perna viridis from the coastal waters of Malaysia: a review based on 1998 data - Yap, Chee Kong (Sciencedomain International, 2014)
Since 1990s until today, the Asia-Pacific Mussel Watch approach has been widely used for biomonitoring purpose in Malaysia by using the green-lipped mussel Perna viridis in particular. This paper reviewed the concentrations of heavy metals (Cd, Cu, Pb and Zn), Linear Alkylbenzenes (LABs), Polycyclic Aromatic Hydrocarbons (PAHs), phenolic Endocrine Disrupting Chemicals (EDCs) [nonylphenol (NP), octylphenol (OP), and bisphenol A (BPA)] and organochlorine (OC) compounds (PCBs, DDTs, CHLs, HCHs and HCB) in nine mussel populations collected in 1998 (because I involved in the sampling field trip when I was a trainee researcher) from the coastal waters of Malaysia. In fact, all of these data were published separately in five different peer-reviewed journals in the literature (see Yap et al. [6,7]; Tsutsumi et al. [14]; Isobe et al. [15]; Monirith et al. [16]). Since they discussed only based on the group of contaminants which they focused upon, this review paper aimed to see a holistic picture and understanding of the impacts of the different chemical contaminants in relation to the description of the sampling sites. Based on seven mussel populations with complete 11 chemicals (ranging from heavy metals, LABs, PAHs, phenolic EDCs and OCs), a dendrogram was established using single linkage cluster analysis. A dendrogram was established using single linkage cluster analysis showing two major subclusters. The first subcluster comprised Tanjung Rhu, Trayong, Kuala Penyu and Pasir Panjang populations, indicating relatively uncontaminated conditions while the other subcluster consists of Penang, Kg. Pasir Puteh and Anjung Batu which indicated contaminated conditions as it is well supported by the elevated levels of some chemicals. The subcluster combining Penang and Kg. Pasir Puteh populations were mainly due to the elevated levels of LABs and PAHs in both sites while Kg. Pasir Puteh also had elevated levels of Cu, Pb, PCBs and CHLs. Anjung Batu, which is also clustering together with Penang and Kg. Pasir Puteh population can be explained by its elevated levels of three OC compounds namely DDTs, CHLs and HCHs.